A novel method to in vitro evaluate biocompatibility of nanoscaled scaffolds. Issue 9 (19th April 2016) - Li, Xiaoming; Wang, Zheng; Zhao, Tianxiao; Yu, Bo; Fan, Yubo; Feng, Qingling; Cui, Fu‐zhai; Watari, Fumio
Abstract: This study provided a new method to in vitro evaluate the biocompatibility of nanoscaled scaffolds for tissue engineering with neutrophils other than ordinary cell culture. The neutrophils were separated from human peripheral blood of healthy subjects. In vitro degradation product of nanohydroxyapatite/collagen (nHAC), nanohydroxyapatite/collagen/poly (L‐lactic acid) (nHACP), and nHACP reinforced by chitin fibers (nHACP/CF) in the D‐Hank's Balanced Salt Solution (D‐HBSS) was used as the testing solution, which was thereafter mixed with the neutrophils. It was shown that the cell survival rate in the testing solutions had no significant difference from that in the D‐HBSS (control). However, from both gene and protein expression levels, the lactate dehydrogenase and tumor necrosis factor‐alpha of the neutrophils in the nHACP/CF testing solution were found lowest during the whole testing period; the main reasons of which might be that the calcium release rate of the scaffold was slowest and that the pH value of its degradation solution was nearest to that of human body. Moreover, in vivo experiments showed that most inflammation reactions happened for nHAC and poly (L‐lactic acid) groups, while the least inflammation reactions happened for nHACP/CF group in the subcutaneous dorsum of mice at 2 weeks after the surgery, which confirmed the in vitro findings. These results indicated that the pH value and the certain metal iron concentration of the nanoscaled scaffold degradation solution should be two important factors that significantly affect its biocompatibility. This study provides a simple and effective biocompatibility test method for biodegradable nanoscaled tissue engineering scaffolds. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2117–2125, 2016.